An Equivalence Trial Comparing Instructor-Regulated With Directed Self-Regulated Mastery Learning of Advanced Cardiac Life Support Skills. Issue 4 (August 2015) - Devine, Luke A.; Donkers, Jeroen; Brydges, Ryan; Perelman, Vsevolod; Cavalcanti, Rodrigo B.; Issenberg, S. Barry
Abstract : Introduction: Instructor-led simulation-based mastery learning of advanced cardiac life support (ACLS) skills is an effective and focused approach to competency-based education. Directed self-regulated learning (DSRL) may be an effective and less resource–intensive way to teach ACLS skills. Methods: Forty first-year internal medicine residents were randomized to either simulation-based DSRL or simulation-based instructor-regulated learning (IRL) of ACLS skills using a mastery learning model. Residents in each intervention completed pretest, posttest, and retention test of their performance in leading an ACLS response to a simulated scenario. Performance tests were assessed using a standardized checklist. Residents in the DSRL intervention were provided assessment instruments, a debriefing guide, and scenario-specific teaching points, and they were permitted to access relevant online resources. Residents in the IRL intervention had access to the same materials; however, the teaching and debriefing were instructor led. Results: Skills of both the IRL and DSRL interventions showed significant improvement after the intervention, with an average improvement on the posttest of 21.7%. After controlling for pretest score, there was no difference between intervention arms on the posttest [ F (1, 37) = 0.02, P = 0.94] and retention tests [ F (1, 17) = 1.43, P = 0.25]. Cost savings were realized in the DSRL intervention after the fourth group (16 residents) had completed each intervention, with an ongoing savings of 80 per resident. Conclusions: Using a simulation-based mastery learning model, we observed equivalence in learning of ACLS skills for the DSRL and IRL conditions, whereas DSRL was more cost effective. Abstract : Supplemental digital content is available in the text.